Conceptualization of a HOTS-Based Tashbih Assessment Model: Instrument Gap Analysis in The Balāghah Textbook - Subhi, Muhamad Subhi; Hamaz, Nirmala Luthfia; Noval, Ahmad; Zamakhsari, Zamakhsari (Universitas Negeri Padang, 2026)
Developing critical thinking skills in Arabic language learning is currently a curriculum requirement, but the quality of the assessment instruments in textbooks is often suboptimal in stimulating these skills. This study aims to identify gaps (needs analysis) in the assessment instruments for Tashbih (التشبيه) material in the Balāghah Grade XII Madrasah Aliyah Religious Specialization textbook as a basis for formulating an innovative assessment model based on Higher-Order Thinking Skills (HOTS). The method used was Qualitative Content Analysis of 28 Tashbih questions in the textbook, which was carried out by classifying the questions according to Bloom’s Revised Taxonomy (C1-C6) and the measurement’s focus. The results revealed a significant gap: the majority of assessment instruments (85%) were dominated by low cognitive levels (LOTS/C1-C2) and intermediate levels (MOTS/C3), focusing on memorization and simple identification of the pillars of Tashbih. Conversely, the measurement of the ability to analyze rhetorical functions, evaluate context, and create (HOTS: C4, C6) only reached 15%. Based on these findings, this study recommends the conceptualization of a Tashbih Rhetorical Analysis Project Assessment Model. This prototype model focuses on HOTS-based instruments that require students to compare, evaluate, and create Tashbih in authentic texts (Al-Qur’an/Hadith), supported by an assessment rubric that measures the depth of meaning analysis (Wajhu Shabh). This conceptualization is expected to serve as a guide for assessment innovation to improve students’ critical thinking skills in understanding Balāghah.